2021
DOI: 10.3390/inventions6040062
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Power Generation Using a Nitrogen Turbine Engine Instead of a Conventional Injection Steam Turbine Engine

Abstract: An ever-increasing demand for electrical power and soaring levels of energy consumption around the world have led to an energy crisis. Thus, this paper aims to review the conventional technologies against those of newer developments in electrical power generation such as using nitrogen generators. The nitrogen generator method is most appealing as it is a seemingly free energy already existing in nature. A nitrogen generator with a 5000 (Nm3/h) capacity has the potential to be used to analyze gas composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, to be competitive with a group of advanced power generation technologies [76,77] such as solar, wind, hydro, and nuclear power, and newly discovered sustainable clean energy technologies such as nitrogen power, the key issue is the cost to the consumer. When comparing estimates in terms of operating costs per unit of electricity kw/h/USD and comparing the costs for building a power plant per unit of Mwe/USD [1,78], it was found that solar power had the highest operating costs, including expenses such as maintenance of technology materials, and labor costs of approximately 0.181 kw/h/USD and an estimated 600,000 Mwe/USD in investment cost for power plant construction. [7].…”
Section: A Comparative Analysis Of Power Plant Costs Between Existing...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, to be competitive with a group of advanced power generation technologies [76,77] such as solar, wind, hydro, and nuclear power, and newly discovered sustainable clean energy technologies such as nitrogen power, the key issue is the cost to the consumer. When comparing estimates in terms of operating costs per unit of electricity kw/h/USD and comparing the costs for building a power plant per unit of Mwe/USD [1,78], it was found that solar power had the highest operating costs, including expenses such as maintenance of technology materials, and labor costs of approximately 0.181 kw/h/USD and an estimated 600,000 Mwe/USD in investment cost for power plant construction. [7].…”
Section: A Comparative Analysis Of Power Plant Costs Between Existing...mentioning
confidence: 99%
“…Nuclear power had the cheapest operating costs at 0.030 kw/h/USD but the most expensive cost for power plant construction at roughly 5,000,000 Mwe/USD. Finally, nitrogen power had overhead operating costs of 0.045 kw/h/USD and projected investment expenses for power plant construction of 2,000,000Mwe/USD [1], as shown in Table 7. A comparative analysis of the cost of power plant technology found that energy storage and renewable electric motor power have operating costs, including expenses such as the maintenance of equipment and labor of 0.030 kw/h/USD and an estimated cost of investing in the construction of a power plant at 1,500,000 Mwe/USD.…”
Section: A Comparative Analysis Of Power Plant Costs Between Existing...mentioning
confidence: 99%
See 2 more Smart Citations